How Governor Directives Changed Health Workforce Flexibility in Response to the COVID-19 Pandemic. (May 2023) - Ziemann, Margaret; Strasser, Julia; Krips, Maddie; Yang, Y. Tony; Pittman, Patricia
Objectives: In times of heightened population health needs, the health workforce must respond quickly and efficiently, especially at the state level. We examined state governors' executive orders related to 2 key health workforce flexibility issues, scope of practice (SOP) and licensing, in response to the COVID-19 pandemic. Methods: We conducted an in-depth document review of state governors' executive orders introduced in 2020 in all 50 states and the District of Columbia. We conducted a thematic content analysis of the executive order language using an inductive process and then categorized executive orders by profession (advanced practice registered nurses, physician assistants, and pharmacists) and degree of flexibility granted; for licensing, we indicated yes or no for easing or waiving cross-state regulatory barriers. Results: We identified executive orders in 36 states containing explicit directives addressing SOP or out-of-state licensing, with those in 20 states easing regulatory barriers pertaining to both workforce issues. Seventeen states issued executive orders expanding SOP for advanced practice nurses and physician assistants, most commonly by completely waiving physician practice agreements, while those in 9 states expanded pharmacist SOP. Executive orders in 31 states and the District of Columbia eased or waived out-of-state licensing regulatory barriers, usually for all health care professionals. Conclusion: Governor directives issued through executive orders played an important role in expanding health workforce flexibility in the first year of the pandemic, especially in states with restrictive practice regulations prior to COVID-19. Future research should examine what effects these temporary flexibilities may have had on patient and practice outcomes or on permanent efforts to relax practice restrictions for health care professionals.